RELATIVE EFFICACY OF SYSTEMIC AND NON-SYSTEMIC FUNGICIDES AGAINST FUSARIUM OXYSPORUM AND F. SOLANI AFFECTING TOMATO - B. KUMAR, I. J. KAPOOR and (Indian Phytopathology, 2002)
Relative efficacy of three systemic (benomyl, carbendazim, and thiophanatemethyl) and three non-systemic (captafol, captan and thiram) fungicides against two isolates each of Fusarium oxysporum and F. solani obtained from tomato was studied using poison food technique. Carbendazim and benomyl were most toxic. F. solani isolate KHFs-41 was most sensitive, whereas F. oxysporum isolate DFo-13 was least sensitive to these fungicides. F. solani isolates required 3-5 times more dosages of non-systemic fungicides than F. oxysporum isolates. The decreasing order of overall efficacy of different fungicides was carbendazim, benomyl, captatol, thiram, thiophanate-methyl and captan.